WEB-BASED INDEPENDENT LEARNING METHODS FOR ENGLISH VOCABULARY ACQUISITION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the context of digital transformation in education, web-based independent learning has emerged as a vital approach to enhance students' lexical competence in English. This article explores effective strategies, tools, and platforms that facilitate autonomous vocabulary acquisition and assesses their pedagogical implications. The study also presents practical recommendations for integrating these methods into higher education curricula.